Application of the Habitat-Hectare Method in environmental compensation: The case of the Río Piedras Reservoir, Costa Rica - Bonilla, Fabián (2022)
Introduction: Environmental compensation is the final alternative to face the impacts of development projects that cannot be avoided, reduced, or mitigated. The offset of affected habitats or environmental elements usually substitutes ecologically equivalent resources. The Habitat-Hectare Method was initially designed to assess the ecological equivalence of native vegetation, and employs indicator scores relative to a reference habitat. The sum of these scores measures the structural condition of the environment against the reference, quantifying the number of hectares needed to compensate for the loss of similar habitat. Although it is not exempt from limitations, the values can be estimated from field data collected without ambiguity, in a reproducible way, with less bias than more qualitative methods. In this paper, we use a modification of the Habitat-Hectare Method to determine the equivalent area needed to compensate for habitat loss in a protected wilderness in Costa Rica.  Methods: We worked in the Lomas de Barbudal Biological Reserve, north Pacific of Costa Rica, a protected wilderness where nearly 113 hectares will be flooded for the Río Piedras Reservoir. In a property previously identified as a potential compensation site, we assessed indicators for landscape, soil, vegetation structure, and ecosystem services; the scores were assigned in relation to the environment found at the flood site.  Results: The environmental condition score at the compensation site was 44.7% (±15.9%) of the impact site. Consequently, considering the uncertainty in our measurements, compensating for the loss of each hectare would require between 2.23 and 3.49 hectares of a similar environment.  Conclusion: Between 2.23 and 3.49 hectares of are needed to compensate for the loss of habitat in the Río Piedras Reservoir.